Control of stenting procedures with optical imaging - Cysewska-Sobusiak, Anna Romana (Photonics Letters of Poland, 2020)
The article presents how application of optical methods of imaging may aid control of more and more widespread stenting procedure. Modern gastro-videoendoscopy is especially useful in such therapeutic effects made in particular parts of the alimentary tract. The shown selected examples relate to results of real studies made in cooperation with medical specialists Full Text: PDF References A. Cysewska-Sobusiak, "Examples of acquisition and application of biooptical signals", Phot. Lett. Poland 11, 2 (2019). CrossRef P. Listewnik and A. Mazikowski, "Automatic system for optical parameters measurements of biological tissues", Phot. Lett. Poland 10, 3 (2018). CrossRef J-S. Park, S. Jeong, and D. H. Lee, "Recent Advances in Gastrointestinal Stent Development", Clin. Endosc. 48, 3 (2015). CrossRef B.S. Dhillon, "Medical device reliability and associated areas" (Boca Raton, CRC Press LLC 2000). CrossRef J.F. Rey, R. Lambert, and The ESGE Quality Assurance Committee, "ESGE Recommendations for Quality Control in Gastrointestinal Endoscopy: Guidelines for Image Documentation in Upper and Lower GI Endoscopy", Endoscopy 33 (2001). CrossRef W.M. Saltzman, "Biomedical engineering. Bridging medicine and technology" (Cambridge University Press 2009). CrossRef F.A. Duck, "Physical properties of tissue: a comprehensive reference book" (San Diego, Academia Press 1990). CrossRef A. Cysewska-Sobusiak, "One-dimensional representation of light-tissue interaction for application in noninvasive oximetry", Opt. Eng. 36, 4 (1997). CrossRef A. Cysewska-Sobusiak, P. Skrzywanek, and A. Sowier, "Utilization of Miniprobes in Modern Endoscopic Ultrasonography", IEEE Sensors Journal 6, 5 (2006). CrossRef T. Mahmood, M.A. Scaffidi, R Khan, and S.Ch. Grover, "Virtual reality simulation in endoscopy training: Current evidence and future directions", World Journal of Gastroenterol. 24, 48 (2018). CrossRef https://medical.olympusamerica.com DirectLink